2018
DOI: 10.1002/sim.7601
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing performance of BreastScreen Norway using value of information in graphical models

Abstract: This study proposes a method to optimize the performance of BreastScreen Norway through a stratified recommendation of tests including independent double or single reading of the screening mammograms and additional imaging with or without core needle biopsy. This is carefully evaluated by a value of information analysis. An estimated graphical probabilistic model describing the relationship between a set of risk factors and the corresponding risk of breast cancer is used for this analysis, together with a Baye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 19 publications
2
0
0
Order By: Relevance
“…That HT, in addition to age, appeared as the most influential risk factor for breast cancer among women with a benign or premalignant lesion, is in line with a previous study 45 on stratified screening based on prior screening results, age and self-reported physical activity, BMI, smoking, HT, family history of breast cancer and reproductive history.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…That HT, in addition to age, appeared as the most influential risk factor for breast cancer among women with a benign or premalignant lesion, is in line with a previous study 45 on stratified screening based on prior screening results, age and self-reported physical activity, BMI, smoking, HT, family history of breast cancer and reproductive history.…”
Section: Discussionsupporting
confidence: 89%
“…The effect of other types of HT (estrogen not in combination with progestin) and prior HT use was smaller and did not reach statistical significance, however still indicated an increased risk. That HT, in addition to age, appeared as the most influential risk factor for breast cancer among women with a benign or premalignant lesion, is in line with a previous study 45 on stratified screening based on prior screening results, age and self‐reported physical activity, BMI, smoking, HT, family history of breast cancer and reproductive history. However, our results are contrasting a previous study reporting decreased risk of progression to invasive breast cancer among HT users at diagnosis of carcinoma in situ 28 (proposedly through removal of the main etiological driver as the women quit their use of HT).…”
Section: Discussionsupporting
confidence: 88%